2D Janus Transition Metal Dichalcogenides: Properties and Applications. Issue 4 (27th January 2022) - Tang, Xiao; Kou, Liangzhi
Abstract : The successful fabrication of Janus transition metal dichalcogenide (TMD) monolayer has sparked extensive research interests in various fields, such as nanoelectronics, optoelectronics, valleytronics, and catalysis. Janus TMDs can not only inherit the advantages of conventional TMDs but also produce novel properties which are different from their counterparts. The breaking of vertical mirror symmetry can induce a variety of novel properties, such as Rashba spin splitting, vertical piezoelectricity, and long exciton lifetime. Moreover, the intrinsic electric field that originates from the vertical asymmetry can serve as a superior platform for tuning the interlayer coupling when forming van der Waals structures. In this mini review, the recent key research progresses of 2D Janus TMDs, including the fundamental properties and potential applications, are briefly summarized, and the existing challenges are also presented. Abstract : Due to the out‐of‐plane asymmetry, Janus transition metal dichalcogenides monolayers possess the intrinsic dipole moment, which can induce many novel properties, exhibiting great potentials in gas sensors, spintronics, nanoelectromechanics, (opto‐)electronics, and catalysis. Moreover, the built‐in electric field can act as an alternative way to tune the interlayer interactions in Janus van der Waals (vdW) structures, opening new possibilities for applications.